(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This research paper highlights the need for comprehensive improvement of financial, legal, and technical-economic mechanisms to effectively finance investment projects in the real sector. It provides a scientific rationale for addressing the challenges associated with financing such projects and presents research-based conclusions in this area.